1982
DOI: 10.1073/pnas.79.4.1012
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between structure of the 5' noncoding region of viral mRNA and efficiency in the initiation step of protein synthesis in a eukaryotic system.

Abstract: To determine whether the rate of protein synthesis is controlled by the structure ofmRNA near its 5' terminus, protein-synthesizing ability, especially in its initial stage, was compared among RNAs of plant viruses. Those viruses used here contain several definite pieces of single-stranded RNA. Each of these RNAs acts as a messenger. Cucumber mosaic virus (CMV) RNA 5 synthesizes a small amount of a protein, Mr 7000, in an in vitro protein-synthesizing system from wheat germ or reticulocyte. Brome mosaic virus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1982
1982
2015
2015

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…Before concluding that the putative Shine-Dalgarno sequence plays no role, however, it will be necessary to quantitate the yield of protein from the wild-type and mutant viral mRNAs. Yamaguchi et al (537) recently attempted to correlate the translational efficiency of two plant virus mRNAs with the presence or absence of a sequence complementary to the 3' end of 18S rRNA, but they presented no evidence that the AUG triplet on which they focused is the functional initiator codon in cucumber mosaic virus RNA-5. Thus, the case for a Shine-Dalgarno interaction in eucaryotes is not strong.…”
Section: The Initiation Processmentioning
confidence: 99%
“…Before concluding that the putative Shine-Dalgarno sequence plays no role, however, it will be necessary to quantitate the yield of protein from the wild-type and mutant viral mRNAs. Yamaguchi et al (537) recently attempted to correlate the translational efficiency of two plant virus mRNAs with the presence or absence of a sequence complementary to the 3' end of 18S rRNA, but they presented no evidence that the AUG triplet on which they focused is the functional initiator codon in cucumber mosaic virus RNA-5. Thus, the case for a Shine-Dalgarno interaction in eucaryotes is not strong.…”
Section: The Initiation Processmentioning
confidence: 99%
“…This complementarity is thought to facilitate the binding of mRNA to ribosomes. The situation in eucaryotes is less certain since the presence of a sequence complementary to 18S rRNA is variable (17,46). For this reason, it was of interest to examine the leader sequences of early vaccinia virus mRNAs.…”
Section: Downloaded Frommentioning
confidence: 99%
“…The CMV-Ar isolate from Lorestan province fell into subgroup IA, whereas CMV-Ar and CMV-Rs isolates fell into subgroup IB (Figure 1). The conserved hexanucleotide sequence (5′-TCGTAG-3′) upstream of the CP gene start codon that is involved in 18S ribosomal RNA binding in subgroup I (Yamaguchi et al 1982) was only found in subgroup IA isolates, but not in any of the subgroup IB isolates (data not shown).…”
Section: Phylogenetic Treementioning
confidence: 81%